Uncovering the hidden mechanics of upper body rotations in tennis serves using wearable sensors on Dutch professional players - van Trigt, B.; Faneker, E.; Leenen, A. J. R.; Hoekstra, A. E.; Hoozemans, M. J. M. (Frontiers in Sports and Active Living, 2025)
Background: It is assumed that the tennis serve is performed according to the kinetic chain principle in which a proximal-to-distal sequence in peak angular velocities of subsequent body segments can be observed to reach high end point ball velocities. The aim of the present study was to investigate if the magnitude and (intersegmental) timing of peak angular velocities of body segments in professional tennis players are different between first and second serves and if they are associated with serve performance.